Understanding the effect of Pulsed Electric Fields on multilayered solid plant foods: Bunching onions (Allium fistulosum) as a model system. (June 2019) - Liu, Tingting; Burritt, David John; Oey, Indrawati
Abstract: While it is well known that the nature of the applied electric field and the heterogeneity of the tissue can influence the impact of PEF treatment on the plant tissues found in plant-based foods, few studies have investigated the influence of PEF on plant structures that are made up of multiple structurally similar organs. The aim of this study was to understand the effect of pulsed electric fields (PEF), at different electric field strengths (0, 0.3, 0.7 and 1.2 kV/cm) and specific energy (7, 21 and 52 kJ/kg), on a multilayered plant material, with bunching onion bulb tissues being used as a model system. The present study found that carbohydrates leakage was an appropriate index to assess PEF induced damage and that plasmolysis of epidermal cells was a good indicator of plasma membrane integrity after PEF. In addition, electric field strength had a greater impact on the cell integrity than specific energy applied. While other studies have shown that different cell types have different sensitivities to PEF, using plasmolysis as an indicator of cell damage, this study clearly showed that the same PEF treatment conditions had a greater effect on the epidermal cells of the outer scales compared to the inner scales. Hence, while different plant cell types vary in their sensitivities to PEF the spatial location of the same cell type within a complex plant material made up of multiple similar organs, i.e. an onion bulb, can also influence how cells respond to the PEF treatment. Despite PEF induced disruption at the cellular level being detected by carbohydrate leakage, the epidermal cell plasmolysis test and by cryo-scanning electromicroscopy (cryo-SEM), no gross structural changes at the organ level were observed using cryo-SEM or fluorescence microscopy. This study also reports for the first time that PEF treatment can enhance fructan leakage from onion bulbs, which means that PEF treatments have the potential to manipulate the fructan contents of some plant-based foods. Graphical abstract: Unlabelled Image Highlights: Electric field strength had a greater impact on cell membrane permeability than specific energy input. The effect of PEF treatment on epidermal cells increased from the outer to inner scale leaves. The effect of PEF on the same tissue type depended on the location of the tissue within the same bulb. Increasing the electric field strength increased fructan leakage.